PENGARUH DIGITAL MARKETING PADA APLIKASI TIKTOK DAN LITERASI KEUANGAN TERHADAP KINERJA UMKM - Harina, Harina; Reza Widhar Pahlevi, (JEMBA: JURNAL EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2023)
The use of digital technology, especially through the TikTok platform, has provided new opportunities for Micro, Small and Medium Enterprises (MSMEs) to expand their market reach and improve their performance. In addition, financial literacy is also an important factor in the financial management of MSMEs. Therefore, this study aims to investigate the effect of digital marketing through the TikTok application and financial literacy on MSME performance. In this study, a quantitative research approach with purposive sampling method was used to select 91 respondents from the Corporate Social Responsibility (CSR) Department of PT Indomoro Kencana in Murung Raya Regency, Central Kalimantan Province. Primary data was obtained through interviews and distributing questionnaires to MSME actors, while secondary data was obtained from the MSME Office and scientific journals. Data analysis was conducted with validity test, reliability test, multiple linear regression analysis, hypothesis testing t (T-Test) and F test (F-Test), and coefficient of determination (R2) analysis. The results show that both digital marketing and financial literacy have a significant influence on MSME performance partially. This finding suggests that the implementation of digital marketing strategies can increase the visibility and interaction of MSMEs with consumers through digital platforms. In addition, good financial literacy helps MSMEs optimize their financial management and make better financial decisions. Simultaneously, both variables also have a significant effect on MSME performance together. In conclusion, this study emphasizes the importance of using effective digital marketing strategies and improving financial literacy in supporting MSME performance. The use of digital marketing through the TikTok application provides opportunities for MSMEs to increase visibility and interaction with consumers. Meanwhile, good financial literacy helps MSMEs to manage finances efficiently and make the right financial decisions. The combined use of these two aspects can provide greater benefits for MSMEs in achieving their business growth and success.